Estimates of prediabetes and undiagnosed type 2 diabetes in Denmark: The end of an epidemic or a diagnostic artefact?. Issue 1 (February 2020) - Jørgensen, Marit Eika; Ellervik, Christina; Ekholm, Ola; Johansen, Nanna Borup; Carstensen, Bendix
Background: Up-to-date information on undiagnosed type 2 diabetes and prediabetes based on current diagnostic criteria is lacking. The study aimed to model the total numbers of people with undiagnosed type 2 diabetes and prediabetes in Denmark based on existing population-based surveys. Methods: Two population-based Danish studies with information on HbA1c, date of examination, gender, age and known type 2 diabetes were identified: the Danish General Suburban Population Study, n = 21, 205, and the Danish Health Examination Survey, n = 18, 065. The prevalence of known, undiagnosed and pre-diabetes were estimated in the Danish General Suburban Population Study, and population-level age-specific prevalence of known type 2 diabetes was estimated from national registers. The Danish Health Examination Survey was included for sensitivity analysis. Combining estimates of the survey participation rate among known type 2 diabetes patients with known overall participation rates from the studies allowed for the correction of survey prevalence to plausible population-level estimates of age- and gender-specific prevalence. Results: The prevalence of known, undiagnosed and pre-diabetes was highest among men, increasing with age with a peak at age 70. Applying the survey-based prevalence to the entire Danish population, the estimated number (May 2011) with undiagnosed type 2 diabetes was 60, 681, corresponding to 24% of all type 2 diabetes cases, and 292, 715 had prediabetes, about 50% more than the total type 2 diabetes population. Conclusions: Estimates of undiagnosed type 2 diabetes and prediabetes are dramatically lower than reported in previous studies (60, 681 vs 200, 000 and 292, 715 vs 750, 000); however, whether this reflects a true decrease in incidence or the change to HbA1c -based diagnostic criteria is not clear.